Notas sobre Gasteromycetes II: Phallus duplicatus Bosc - Martín Esteban, María Paz; Tabarés Carriedo, Manuel (Revista Catalana de Micologia, 2007)
Notes on Gasteromycetes II: Phallus duplicatus Bosc. - A rare and interesting Gasteromycete , Phallus duplicatus Bosc (= Dictyophora duplicata (Bosc) Fischer), collected in Catalonia, is here describ ed and discussed.